Sublimed C60 for efficient and repeatable perovskite-based solar cells - Ahmed A. Said; Erkan Aydin; Esma Ugur; Zhaojian Xu; Caner Deger; Badri Vishal; Aleš Vlk; Pia Dally; Bumin K. Yildirim; Randi Azmi; Jiang Liu; Edward A. Jackson; et al. (Nature Communications)
Abstract Thermally evaporated C60 is a near-ubiquitous electron transport layer in state-of-the-art p–i–n perovskite-based solar cells. As perovskite photovoltaic technologies are moving toward industrialization, batch-to-batch reproducibility of device performances becomes crucial. Here, we show that commercial as-received (99.75% pure) C60 source materials may coalesce during repeated thermal evaporation processes, jeopardizing such reproducibility. We find that the coalescence is due to oxygen present in the initial source powder and leads to the formation of deep states within the perovskite bandgap, resulting in a systematic decrease in solar cell performance. However, further purification (through sublimation) of the C60 to 99.95% before evaporation is found to hinder coalescence, with the associated solar cell performances being fully reproducible after repeated processing. We verify the universality of this behavior on perovskite/silicon tandem solar cells by demonstrating their open-circuit voltages and fill factors to remain at 1950 mV and 81% respectively, over eight repeated processes using the same sublimed C60 source material. Notably, one of these cells achieved a certified power conversion efficiency of 30.9%. These findings provide insights crucial for the advancement of perovskite photovoltaic technologies towards scaled production with high process yield.